Considerations about bisphosphonate therapy and patients using dental prosthesis: a literature review - da Silva Maganhoto, Ananda; Garcia Margute, Túlio; Quirino Mota da Silva, Thiago; Rabenschlag Rossato, Andrei; Fonseca dos Santos, Igor; Garcia Margute, Tiago (Brazilian Journal of Case Reports, 2021)
Bisphosphonates are drugs used for treatment of many medical diseases; their prescription has increased over the years due to the various indications for use. They come in two distinct groups: containing nitrogen (alendronate, ibandronate, pamidronate, risedronate and zolendronate) and without nitrogen in their composition (etidronate and tiludronate). Despite being used in the treatment of several diseases, they can lead to the development of osteonecrosis in the patient's maxilla and/or mandible, when submitted to dental procedures, such as extractions, surgeries or traumas for non-adapted prostheses. It is recommended that patients who use bisphosphonates visit the dentist at least once a year, for better control and monitoring of oral health.